(3x+6)+(x-10)+(x-11)=180

Simple and best practice solution for (3x+6)+(x-10)+(x-11)=180 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3x+6)+(x-10)+(x-11)=180 equation:


Simplifying
(3x + 6) + (x + -10) + (x + -11) = 180

Reorder the terms:
(6 + 3x) + (x + -10) + (x + -11) = 180

Remove parenthesis around (6 + 3x)
6 + 3x + (x + -10) + (x + -11) = 180

Reorder the terms:
6 + 3x + (-10 + x) + (x + -11) = 180

Remove parenthesis around (-10 + x)
6 + 3x + -10 + x + (x + -11) = 180

Reorder the terms:
6 + 3x + -10 + x + (-11 + x) = 180

Remove parenthesis around (-11 + x)
6 + 3x + -10 + x + -11 + x = 180

Reorder the terms:
6 + -10 + -11 + 3x + x + x = 180

Combine like terms: 6 + -10 = -4
-4 + -11 + 3x + x + x = 180

Combine like terms: -4 + -11 = -15
-15 + 3x + x + x = 180

Combine like terms: 3x + x = 4x
-15 + 4x + x = 180

Combine like terms: 4x + x = 5x
-15 + 5x = 180

Solving
-15 + 5x = 180

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '15' to each side of the equation.
-15 + 15 + 5x = 180 + 15

Combine like terms: -15 + 15 = 0
0 + 5x = 180 + 15
5x = 180 + 15

Combine like terms: 180 + 15 = 195
5x = 195

Divide each side by '5'.
x = 39

Simplifying
x = 39

See similar equations:

| .02f+0.6(f+20)=-8+0.4f | | Y+6=-4(x-4) | | 6n-60=0 | | 24=-4(3w+3) | | 2y=-4x-6 | | 6[x-1]=9[x-4] | | -10n+12=-3n-9 | | 3c+15-2=2c+12+2 | | 4y-3x=24 | | n-15.43=-9.2 | | 4b+24=2b+10+2 | | 35=7v-6 | | 2X+18=2x-3 | | (2x)=(y-x) | | 9x+15=15x | | 8x+4-8=4x+12 | | R=2m+2s | | x+69=0 | | 2y=(4x^2)-6 | | 2x-2-x=4+4x+6 | | (-9)2(-1)5= | | 3x^2+22x+4=-20 | | x+14=(-6) | | (2y-5)+(9y-8)= | | 2(3)+2w=46 | | 5y+5+2=4y+8-6 | | 6sin^2(3x)=3 | | 3.14r*2=314 | | 2l+2(150)=p | | 3(5)-y=17 | | 7-5p=28 | | 3a+b+5=2a+4 |

Equations solver categories